Hiponatremia - Romero P., Carlos; Salech M., Felipe; Segovia R., Erico (Revista Hospital Clínico Universidad de Chile, 2012)
Alterations in plasma osmolality are related to changes in cell volume , which are the pathophysiological substrate of serious diseases. Under normal conditions sodium is the main determinant of plasma osmolality, and its homeostasis depends primarily on water balance. Hyponatremia is common in clinical practice, and is associated with morbidity and mortality by itself or in relation to its treatment. Despite this, sodium disorders are underdiagnosed, undertreated, and often handled improperly. Because multiple conditions with different treatments can be manifested through hyponatremia, the clear understanding of the pathophysiologic condition of each patient is essential for proper management. This review will discuss the pathophysiology, diagnostic approaches and current therapies of hyponatremia.